Coffee Farming Institutions in Sukamanah Village, Sindangkasih, Ciamis Regency - Sanudin Sanudin, S. Hut., M. Si (Jurnal Agroforestri Indonesia, 2021)
Forestry partnership is a form of social forestry management that provides space for larger communities to be involved in forest management. This study aims to determine the condition of coffee farming institutions in the social forestry program. This research was conducted in May 2021 at the Forest Village Community Institute (LMDH) Sarimukti, Sukamanah Village, Sindang Kasih District, Ciamis Regency. This LMDH was chosen because it has obtained a Social Forestry permit for the Recognition of Forestry Partnership Protection (KULIN-KK) scheme. The results showed that institutionally, LMDH Sarimukti has a good condition because it already has statutes (AD) and bylaws (ART) and the community gets many benefits from its existence so that it is expected to encourage community participation in achieving the goals of social forestry management in the KULIN KK scheme. Socially and economically, the community has started to feel the benefits of the KULIN KK scheme of social forestry management through the production of coffee and other crops. Permission to access arable land through the SK KULIN KK provides peace and comfort for the community to be involved in forest management.